Variety of RNAs in Peripheral Blood Cells, Plasma, and Plasma Fractions. (3rd January 2017) - Savelyeva, Anna V.; Kuligina, Elena V.; Bariakin, Dmitry N.; Kozlov, Vadim V.; Ryabchikova, Elena I.; Richter, Vladimir A.; Semenov, Dmitry V.
Abstract : Human peripheral blood contains RNA in cells and in extracellular membrane vesicles, microvesicles and exosomes, as well as in cell-free ribonucleoproteins. Circulating mRNAs and noncoding RNAs, being internalized, possess the ability to modulate vital processes in recipient cells. In this study, with SOLiD sequencing technology, we performed identification, classification, and quantification of RNAs from blood fractions: cells, plasma, plasma vesicles pelleted at 16, 000g and 160, 000g, and vesicle-depleted plasma supernatant of healthy donors and non-small cell lung cancer (NSCLC) patients. It was determined that 16, 000g blood plasma vesicles were enriched with cell-free mitochondria and with a set of mitochondrial RNAs. The variable RNA set of blood plasma 160, 000g pellets reflected the prominent contribution of U1, U5, and U6 small nuclear RNAs' fragments and at the same time was characterized by a remarkable depletion of small nucleolar RNAs. Besides microRNAs, the variety of fragments of mRNAs and snoRNAs dominated in the set of circulating RNAs differentially expressed in blood fractions of NSCLC patients. Taken together, our data emphasize that not only extracellular microRNAs but also circulating fragments of messenger and small nuclear/nucleolar RNAs represent prominent classes of circulating regulatory ncRNAs as well as promising circulating biomarkers for the development of disease diagnostic approaches.